2000
DOI: 10.1046/j.1365-2281.2000.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between ejection fraction and mitral annulus motion before and after direct‐current electrical cardioversion

Abstract: Mitral annulus motion (MAM) and the relation between left ventricular ejection fraction (EF) and MAM has been shown to differ between patients with sinus rhythm and patients with atrial fibrillation. However, it has not been investigated how the relation between EF and MAM changes on direct-current (DC) electrical cardioversion to sinus rhythm. Therefore, 31 consecutive patients on the waiting list for DC electrical cardioversion were examined by echocardiography before DC electrical cardioversion, and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In critical care settings where acoustic windows are often suboptimal, MAPSE seems to be an attractive parameter. A decreased MAPSE is known to be associated with conditions affecting LV function such as myocardial infarction, heart failure, atrial fibrillation and age [15-17] and its relation to mortality has been described by several studies in patients with cardiovascular disease [15,19-21]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In critical care settings where acoustic windows are often suboptimal, MAPSE seems to be an attractive parameter. A decreased MAPSE is known to be associated with conditions affecting LV function such as myocardial infarction, heart failure, atrial fibrillation and age [15-17] and its relation to mortality has been described by several studies in patients with cardiovascular disease [15,19-21]. …”
Section: Discussionmentioning
confidence: 99%
“…Although MAPSE and LVEF may be related, they are not entirely interchangeable [13,17]. MAPSE is suggested to be primarily representative of subendocardial, longitudinally oriented, myocardial fibres compared to the subepicardial, circumferential fibres measured by LVEF, and is known to detect more subtle abnormalities of LV function [7,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVPD has been shown to be independently associated with the inverse logarithm of early transmitral flow deceleration time in patients with heart failure (HF) [11], and with the severity of LV diastolic impairment in patients with coronary artery disease (CAD) [12]. Notably, left atrial contraction has been proposed to affect AVPD via FrankStarling mechanisms [13], a finding that may explain the presence of reduced AVPD in patients with atrial fibrillation (AF) as compared to age-matched controls in sinus rhythm [14]. Second, AVPD does not correspond to the effective annular excursion occurring during systole.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were included either within a week after an acute myocardial infarction (n=54) or within two weeks before a planned coronary angiography in patients with stable angina (n=35). Since atrial fibrillation has been shown to decrease AV plane displacement disproportionately to left ventricular ejection fraction [12,13], only patients in sinus rhythm were included in the present study.…”
Section: Patientsmentioning
confidence: 99%